The Verilog hardware description language - Thomas, D. E. (Donald E.) 1951- (Kluwer Academic Pub., 2002)
This edition presents the new IEEE 1364-2001 standard of The Verilog Hardware Description Language. It offers updated examples that illustrated the new features of the language as well as a cross- referenced guide to the new and old features.